The Spectrum of Clinical, Immunological, and Molecular Findings in Familial Hemophagocytic Lymphohistiocytosis: Experience From India - Shabrish, Snehal; Kelkar, Madhura; Yadav, Reetika Malik; Bargir, Umair Ahmed; Gupta, Maya; Dalvi, Aparna; Aluri, Jahnavi; Kulkarni, Manasi; Shinde, Shweta; Sawant-Desai, Sneha; Kambli, Priyanka; Hule, Gouri; et al. (Frontiers in Immunology, 2021)
Hemophagocytic lymphohistiocytosis (HLH) is a syndrome of immune dysregulation characterized by hyperactivation of the immune system, excessive cytokine secretion and severe systemic inflammation. HLH is classified as familial (FHL) when associated with mutations in PRF1, UNC13D, STX11 and STXBP2 genes. There is limited information available about the clinical and mutational spectrum of FHL patients in Indian population. This study is a retrospective analysis of 101 molecularly characterized FHL patients over the last 10 years from 20 different referral centres in India. FHL2 and FHL3 together accounted for 84% of cases of FHL in our cohort. Patients belonging to different FHL subtypes were indistinguishable based on clinical and biochemical parameters. However, flow cytometry-based assays viz. perforin expression and degranulation assay were found to be specific and sensitive in diagnosis and classification of FHL patients. Molecular characterization of respective genes revealed 74 76 different disease-causing mutations including 38 39 (51%) novel mutations in PRF1, UNC13D, STX11 and STXBP2 genes. Overall, survival was poor (28%) irrespective of the age of onset or the type of mutation in our cohort. Altogether, this article sheds light on the current scenario of FHL in India. Our data reveal a wide genetic heterogeneity of FHL in the Indian population and confirms the poor prognosis of FHL. This study also emphasizes that though mutational analysis is important for diagnostic confirmation of FHL, flow cytometry based assays help significantly in rapid diagnosis and functional validation of novel variants identified.